(untitled) (Scientific journal of the Fergana State University, 2024)
Nitrogen adsorbed carbon nanotubes attract a lot of attention in the field of materials science due to their unique properties and application possibilities. Therefore, in this work, the influence of various temperatures (i.e. 300, 600 and 900 K) and pressures (1, 5 and 10 bar) on the adsorption of nitrogen atoms on double-layer carbon nanotubes (DSNTS) was investigated. The studies were carried out by the method of molecular dynamics modeling (MD) using the potential (ReaxFF). The results of the studies show that the influence of temperature and pressure on achieving good adsorption of nitrogen atoms on the surface of the DSNT is great, and the best adsorption rate was at a temperature of 300 K and a pressure of 10 bar, which was 79%. . This study helps to understand the interaction of DSNTS with nitrogen atoms depending on external parameters.